Incorporation of hydrogen-producing magnesium into minced beef meat protects the quality attributes and safety of the product during cold storage - Celebi, Yasemin; Kavrut, Enes; Bulut, Menekse; Cetintas, Yunus; Tekin, Ali; Hayaloglu, Ali Adnan; Alwazeer, Duried (Elsevier Sci Ltd, 2024)
The impact of hydrogen (H 2 ) producing magnesium (Mg) incorporation into minced beef meat (MBM) on the quality and safety of the product was investigated. The H 2 -producing Mg (H2-P-Mg)-incorporated MBMs were vacuumed (VP) and stored at 4 degrees C for 12 days. Other MBMs were vacuumed and gassed with H 2 or N 2 . At the end of storage, the lowest browning index values were for H 2 and H2 -P -Mg samples. H2- P - Mg and VP methods generally decreased the counts of mesophilic and psychrotrophic bacteria and yeast molds and restricted the formation of thiobarbituric acid reactive substances and biogenic amines. Heat mapping, PCA, and multivariate analysis methods confirmed chemical analysis results. The volatile compounds were at their highest levels in the control samples at the end of storage, followed by H 2 , N 2 , H2 -P -Mg, and VP samples. Using the H2 -P -Mg method in MBM preparation could protect the quality characteristics and safety of the product during cold storage.
Keywords: Minced beef meat; Biogenic amines; Magnesium; Molecular hydrogen; Nitrogen; Quality attributes